2012
DOI: 10.1093/hmg/dds480
|View full text |Cite
|
Sign up to set email alerts
|

COPI transport complexes bind to specific RNAs in neuronal cells

Abstract: Our fundamental understanding of how several thousand diverse RNAs are recognized in the soma, sorted, packaged, transported and localized within the cell is fragmentary. The COPa and COPb proteins of the coatomer protein I (COPI) vesicle complex were reported to interact with specific RNAs and represent a candidate RNA sorting and transport system. To determine the RNA-binding profile of Golgi-derived COPI in neuronal cells, we performed formaldehyde-linked RNA immunoprecipitation, followed by high-throughput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
1
27
1
Order By: Relevance
“…Autophagy dysfunction is implicated in ALS and in degradation of mSOD1 and mTDP-43 [9], but the underlying mechanisms remain unclear. RNA dysfunction is now widely implicated in ALS and ER-derived vesicles are involved in RNA trafficking [74]. Furthermore, Ypt1 binds to HAC1 RNA and modulates the UPR [75].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy dysfunction is implicated in ALS and in degradation of mSOD1 and mTDP-43 [9], but the underlying mechanisms remain unclear. RNA dysfunction is now widely implicated in ALS and ER-derived vesicles are involved in RNA trafficking [74]. Furthermore, Ypt1 binds to HAC1 RNA and modulates the UPR [75].…”
Section: Discussionmentioning
confidence: 99%
“…Any reads less than 35 bases were discarded. Our experience suggested that this strategy effectively eliminated low‐quality reads while high‐quality regions were retained …”
Section: Methodsmentioning
confidence: 99%
“…Our experience suggested that this strategy effectively eliminated low-quality reads while high-quality regions were retained. [45][46][47] Sequence alignment. The BFAST (http://bfast.sourceforge.net) 48 was used as the primary alignment algorithm because it has high sensitivity for aligning reads on loci containing small insertions and deletions compared to the reference genome (hg19).…”
Section: Measurement Of Mrna Expressionmentioning
confidence: 99%
“…Any read with a length of less than 35 bases was discarded. Our experience suggests that this strategy effectively eliminates low-quality reads while retaining high-quality regions (Breese and Liu, 2013;Juan et al, 2013;Todd et al, 2013).…”
Section: Bioinformatic Analysis Of the Rna-seq Datamentioning
confidence: 99%